Epitranscriptomic regulation of HIV-1 full-length RNA packaging. Issue 4 (8th February 2022) - Pereira-Montecinos, Camila; Toro-Ascuy, Daniela; Ananías-Sáez, Catarina; Gaete-Argel, Aracelly; Rojas-Fuentes, Cecilia; Riquelme-Barrios, Sebastián; Rojas-Araya, Bárbara; García-de-Gracia, Francisco; Aguilera-Cortés, Paulina; Chnaiderman, Jonás; Acevedo, Mónica L; Valiente-Echeverría, Fernando; et al.
Abstract: During retroviral replication, the full-length RNA serves both as mRNA and genomic RNA. However, the mechanisms by which the HIV-1 Gag protein selects the two RNA molecules that will be packaged into nascent virions remain poorly understood. Here, we demonstrate that deposition of N 6 -methyladenosine (m 6 A) regulates full-length RNA packaging. While m 6 A deposition by METTL3/METTL14 onto the full-length RNA was associated with increased Gag synthesis and reduced packaging, FTO-mediated demethylation promoted the incorporation of the full-length RNA into viral particles. Interestingly, HIV-1 Gag associates with the RNA demethylase FTO in the nucleus and contributes to full-length RNA demethylation. We further identified two highly conserved adenosines within the 5′-UTR that have a crucial functional role in m 6 A methylation and packaging of the full-length RNA. Together, our data propose a novel epitranscriptomic mechanism allowing the selection of the HIV-1 full-length RNA molecules that will be used as viral genomes.